2021
DOI: 10.1080/17429145.2021.1974582
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulation of plant sugar transporter genes by beneficial rhizobacteria

Abstract: In their natural environment, plants live in close interaction with complex populations of microorganisms, including rhizobacteria species commonly referred to as 'Plant Growth Promoting Rhizobacteria' (PGPR). A growing body of evidence demonstrates the importance of sugar transport in plant pathogen resistance and in plant-microorganism mutualistic symbioses. Using an in vitro experimental system, including the model plant species Arabidopsis thaliana, two PGPR strains (Pseudomonas simiae PICF7 and Burkholder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…Regarding the potential involvement of VOCs produced by PICF6 and PICF7 in plant growth promotion, 1-decene, a compound elsewhere reported to increase the fresh weight of A. thaliana [ 59 ], was found in the volatilomes of both strains ( Table 2 ). Interestingly, Desrut et al [ 36 ] have recently reported the ability to promote the growth of A. thaliana seedlings by volatiles (not determined) emitted by strain PICF7. As mentioned above for the case of pathogen inhibition, attention should be called here since results may also vary depending on the culturing medium used.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding the potential involvement of VOCs produced by PICF6 and PICF7 in plant growth promotion, 1-decene, a compound elsewhere reported to increase the fresh weight of A. thaliana [ 59 ], was found in the volatilomes of both strains ( Table 2 ). Interestingly, Desrut et al [ 36 ] have recently reported the ability to promote the growth of A. thaliana seedlings by volatiles (not determined) emitted by strain PICF7. As mentioned above for the case of pathogen inhibition, attention should be called here since results may also vary depending on the culturing medium used.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, plant growth was enhanced when Luria–Bertani (LB) and Methyl Red Vogues Proskauer (MR-VP) were used, media that favored the production of the volatile butanediol. Whether 1-decene is produced by strain PICF7 in MS medium (as here reported for NA and PDA media), and whether this compound is the responsible of the growth of A. thaliana seedlings [ 36 ] remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though most of these antagonists originated from the banana rhizosphere soil or banana roots, as native constituents of the root endophytome ( Köberl et al, 2015 , 2017 ; Liu et al, 2019 ; Zhou et al, 2019 ; Kaushal et al, 2020a , b ), some of them were isolated from other plant species. This is the case of the strain Pseudomonas simiae PICF7 (formerly Pseudomonas fluorescens PICF7; Montes-Osuna et al, 2021 ), a highly versatile beneficial endophytic rhizobacteria isolated from olive roots, which display biocontrol and plant-growth-promoting abilities under different experimental conditions ( Maldonado-González et al, 2013 , 2014 , 2015 ; Gómez-Lama Cabanás et al, 2014 , 2018 ; Mercado-Blanco et al, 2016 ; Desrut et al, 2021 ). Recently, strain PICF7 proved to be an effective BCA against Foc STR4, displaying better FWB biocontrol than indigenous rhizobacteria isolated from banana roots ( Gómez-Lama Cabanás et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the role and regulation of sugar transporter activities in plant‐PGPR interactions remain largely unknown (Hennion et al, 2019). Using the model plant Arabidopsis and a collection of PGPR strains, it was recently shown that PGPR can induce major transcriptional changes in plant sugar transport (Desrut et al, 2020; Desrut et al, 2021). Moreover, it was shown that AtSWEET11 and AtSWEET12 , two sugar transporter genes whose expression is repressed by the well‐characterized PGPR strain Pseudomonas simiae WCS417r, are functionally involved in its plant growth‐promoting effects, possibly by controlling the allocation of carbon resources (Desrut et al, 2020).…”
Section: Carbon Fluxes In Roots During Vegetative Developmentmentioning
confidence: 99%